2022
DOI: 10.3390/plants11223157
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Distribution of Tomato Brown Rugose Fruit Virus Infecting Tomato Crop in Saudi Arabia

Abstract: During the growing season of 2021–2022, a total of 145 symptomatic tomato leaf and fruit samples were collected from different locations in Riyadh Region, Saudi Arabia, showing a moderate-to-severe mosaic with dark green wrinkling, blistering, narrowing, and deformation with necrosis spot on tomato leaves, while irregular brown necrotic lesions, deformation, and yellowing spots rendering the fruits non-marketable were observed on tomato fruits. These samples were tested serologically against important tomato v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…On the other hand, a study found that tomato brown rugose fruit virus (ToBRFV) is a serious threat to tomato production in Saudi Arabia. The virus is highly virulent and can infect a wide range of tomato cultivars [ 19 ]. The review by Lv et al [ 20 ] reported the beneficial and harmful effects of Pantoea bacteria on rice growth.…”
mentioning
confidence: 99%
“…On the other hand, a study found that tomato brown rugose fruit virus (ToBRFV) is a serious threat to tomato production in Saudi Arabia. The virus is highly virulent and can infect a wide range of tomato cultivars [ 19 ]. The review by Lv et al [ 20 ] reported the beneficial and harmful effects of Pantoea bacteria on rice growth.…”
mentioning
confidence: 99%